Effects of extracellular metabolic acidosis and out-of-equilibrium CO2/HCO3− solutions on intracellular pH in cultured rat hippocampal neurons - Bouyer, Patrice G.; Salameh, Ahlam I.; Zhou, Yuehan; Kolba, Tiffany N.; Boron, Walter F. (Frontiers in Physiology, 2024)
Metabolic acidosis (MAc)—an extracellular pH (pHo) decrease caused by a [HCO3−]o decrease at constant [CO2]o—usually causes intracellular pH (pHi) to fall. Here we determine the extent to which the pHi decrease depends on the pHo decrease vs. the concomitant [HCO3−]o decrease. We use rapid-mixing to generate out-of-equilibrium CO2/HCO3− solutions in which we stabilize [CO2]o and [HCO3−]o while decreasing pHo (pure acidosis, pAc), or stabilize [CO2]o and pHo while decreasing [HCO3−]o (pure metabolic/down, pMet). Using the fluorescent dye 2',7'-bis-2-carboxyethyl)-5(and-6)carboxyfluorescein (BCECF) to monitor pHi in rat hippocampal neurons in primary culture, we find that—in naïve neurons—the pHi decrease caused by MAc is virtually the sum of those caused by pAc (~70%) + pMet (~30%). However, if we impose a first challenge (MAc1, pAc1, or pMet1), allow the neurons to recover, and then impose a second challenge (MAc2, pAc2, or pMet2), we find that pAc/pMet additivity breaks down. In a twin-challenge protocol in which challenge #2 is MAc, the pHo and [HCO3−]o decreases during challenge #1 must be coincident in order to mimic the effects of MAc1 on MAc2. Conversely, if challenge #1 is MAc, then the pHo and [HCO3−]o decreases during challenge #2 must be coincident in order for MAc1 to produce its physiological effects during the challenge #2 period. We conclude that the history of challenge #1 (MAc1, pAc1, or pMet1)—presumably as detected by one or more acid-base sensors—has a major impact on the pHi response during challenge #2 (MAc2, pAc2, or pMet2).